PO265 Inflammation at the blood-brain barrier: a novel treatment target in traumatic brain injury. (1st December 2017) - Jenkins, Damian; Craner, Matthew; Esiri, Margaret; DeLuca, Gabriele
Abstract : Background: Despite being a devastating disease, traumatic brain injury (TBI) has no effective treatment. Recent interest has focused on two potential therapeutic targets: the blood brain barrier (BBB) and inflammation. It is not known if BBB damage affects inflammation, or if inflammation is helpful or injurious. We hypothesised that BBB damage-induced fibrinogen extravasation drives inflammation and neuronal loss. Methods: Five brain regions from acute (<2 months) and chronic sufferers (>1 year) of TBI were compared with controls. BBB damage, inflammation, neuronal density, and axonal injury were compared quantitatively by immunohistochemistry. Results: 1. Acute TBI caused significant BBB damage, with extravasation of plasma proteins (fibrinogen and IgG) across brain regions. 2. Extravasation of fibrinogen, but not IgG, correlated significantly with microglial activation (rs 0.52 to 0.60, p 0.03) and neuronal loss (rs −0.53 to −0.68, p 0.04). 3. Microglial activation negatively correlated with neuronal density (rs −0.63 to rs −0.77, p 0.006). 4. Trajectory analysis revealed significant spatial overlap between fibrinogen, activated microglia and neuronal loss. 5. No such correlations were found in chronic TBI. 6. No correlation was seen between BBB damage, inflammation and axonal injury. Discussion: BBB damage in acute TBI causes fibrinogen extravasation, microglial activation, and neuronal loss.